Accuracy of ultrasound in antenatal diagnosis of placental attachment disorders. (9th February 2016) - Pilloni, E.; Alemanno, M. G.; Gaglioti, P.; Sciarrone, A.; Garofalo, A.; Biolcati, M.; Botta, G.; Viora, E.; Todros, T.
Abstract: Objectives: To evaluate the accuracy of ultrasound in the diagnosis of placenta accreta and its variants, and to assess the impact of prenatal diagnosis in our population. Methods: A total of 314 women with placenta previa were enrolled prospectively and underwent transabdominal and transvaginal ultrasound examinations. An ultrasound diagnosis (grayscale and color/power Doppler) of placental attachment disorder (PAD) was based on the detection of at least two of the following ('two‐criteria system'): loss/irregularity of the retroplacental clear zone, thinning/interruption of the uterine serosa–bladder wall interface, turbulent placental lacunae with high velocity flow, myometrial thickness < 1 mm, increased vascularity of the uterine serosa–bladder wall interface, loss of vascular arch parallel to the basal plate and/or irregular intraplacental vascularization. Definitive diagnosis was made at delivery by Cesarean section. Maternal outcome in cases diagnosed antenatally was compared with that in cases diagnosed at delivery. Results: There were 37/314 cases of PAD (29 anterior and eight posterior). The two‐criteria system identified 30 cases of placenta accreta, providing a sensitivity of 81.1% and specificity of 98.9%. When anterior and posterior placentae were considered separately, the detection rates of PAD were 89.7 and 50.0%, respectIvely. Maternal outcome was better in women with prenatal diagnosis of PAD, as seen by less blood loss and shorter hospitalization. Conclusions: Our data confirmed that grayscale and color Doppler ultrasound have good performance in the diagnosis of PAD and that prenatal diagnosis improves maternal outcome. Copyright © 2015 ISUOG. Published by John Wiley & Sons Ltd.